Assessment of Household Work as a labour Among homemakers in Cheranalloor Panchayath of Ernakulam District, Kerala - Ammu C , Dr.N.Ajithkumar (International Journal of Advanced Science and Technology, 2020)
Women are considered as the central part of society. They have a vital role in an advanced state of social development and they play different roles in the changing social setup. In their life span, women have performed different roles such as housewives, mothers, in-laws, income sources of the family and rejuvenate a new society. However, in our society family is the priority of every woman and they do all the household activities as their duty. They engage in different kinds of responsibilities in households such as house cleaning, home decorating, preparation of food, washing, take care of children and aged people. These versatile qualities of women make her successful in household work, family life, and social life. Most of the homemakers have some limited resources to do their jobs but in such a way that they perform all the activities differently, every woman has a special skill to manage all these situations. Intelligence is needed for the formation of coordination and integrated team spirit within the family.